The photo-inhibition of camphor leaves (Cinnamomum camphora L.) by NaCl stress based on physiological, chloroplast structure and comparative proteomic analysis - Jiammin Yue; Dawei Shi; Liang Zhang; Zihan Zhang; Zhiyuan Fu; Qiong Ren; Jinchi Zhang (PeerJ, 2020)
Background The distribution and use of camphor (Cinnamomum camphora L.) trees are constrained by increasing soil salinity in south-eastern China along the Yangtze River. However, the response mechanism of this species to salinity, especially in team of photosynthesis, are unknown. Methods Here, we analysed themorphological, physiological, ultrastructural, and proteomic traits of camphor seedlings under NaCl (103.45 mM) treatment in pot experiments for 80 days. Results The growth was limited because of photosynthetic inhibition, with the most significant disturbance occurring within 50 days. Salinity caused severe reductions in the leaf photosynthetic rate (An), stomatal conductance (gs), maximal chlorophyll fluorescence (Fm), maximum quantum yield of PSII (Fv/Fm), non-photochemical quenching (NPQ), relative quantum efficiency of PSII photochemistry (ΦPSII), photochemical quenching coefficient (qP) and photo-pigment contents (chlorophyll a (Cha), chlorophyll b (Chb), total chlorophyll (Chl)); weakened the antioxidant effects, including those of malondialdehyde (MDA), superoxide dismutase (SOD) and peroxidase (POD); and injured chloroplasts. The physiologicalresults indicated that the main reason for photo-inhibition was oxidative factors induced by NaCl. The proteomic results based on isobaric tags for relative and absolute quantitation (iTRAQ) further confirmedthat photosynthesis was the most significant disrupted process by salinity (P < 0.01) and there were 30 downregulated differentially expression proteins (DEPs) and one upregulated DEP related to restraint of the photosynthetic system, which affected photosystem I, photosystem II, the Cytochrome b6/f complex, ATP synthase and the light-harvesting chlorophyll protein complex. In addition, 57 DEPs were related to photo-inhibition by redox effect and 6 downregulated DEPs, including O2 evolving complex 33kD family protein (gi—224094610) and five other predicted proteins (gi—743921083, gi—743840443, gi—743885735, gi—743810316 and gi—743881832) were directly affected. This study provides new proteomic information and explains the possible mechanisms of photo-inhibition caused by salinity on C. camphor.